Osteoarticular tuberculosis of the right foot: a diagnostic delayed - Akil, Natsir; Setiyohadi, Bambang; Lubis, A MT; Fawziah, A (Indonesian Rheumatology Association, 2010)
Extrapulmonary tuberculosis (TB) involving the musculoskeletal system occurs in approximately 1% to 3% of patients with extrapulmonary TB. Concurrent pulmonary or intrathoracic TB is present in less than 50% of cases.1 Spine is the most frequent site of osseous tuberculous involvement. Other affected sites include the hip, knee, foot, elbow, hand, and bursal sheaths.2 Tuberculosis of the foot and ankle remains anuncommon site of the infection, present in 8% to 10% of osteoarticular infection. The diagnosis of osteoarticular tuberculosis is often delayed due to a lack of familiarity with the disease.3 We describe a patient with foot pain and swelling without any respiratory symptom as initial presentation of pulmonary and osteoarticular tuberculosis